Building consensus on principles for international election observation (The Center AtlantaUS, 2006)
Outlines the consensus-building process that led to the endorsement of the Declaration of Principles for International Election Observation and the Code of Conduct for International Election Observers. Highlights some of the continuing challenges facing the election observation community as a whole.
Keywords: ELECTIONS